A naval officer's journal, 1861 (Historia, 2021)
Surgeon Lieutenant R. W. Brigstocke, R.N., was obviously one who enjoyed life, viewing it lightly, unlike many of his fellow-Victorian~. He was keen observer and could put his observations on paper in a graphic manner. This is shown by his journal which is at present in possession of his grand-daughter, Mrs. Barbara Brock of Simon's Town, by courtesy of whom, it is here published. Unfortunately, only seventeen handwritten foolscap pages arc available, for, from its title, it was obviously intended to cover the whole of Brigstocke's stay in Southern Africa. It would appear from the journal that it was commenced at some later date, possibly being written from a diary or notes compiled at the time but for some reason, was never completed.
Keywords: Journal; Surgeon Lieutenant R. W. Brigstocke; Southern Africa